Use of Pedagogical Technologies in the Military Education System (American Scholar: Journal of Interdisciplinary Research and Knowledge, 2026)
The effectiveness of modern military education largely depends on the application of innovative pedagogical technologies that enhance the quality of teaching and learning processes. This article explores the role of pedagogical technologies in the military education system, their advantages, implementation methods, and impact on the professional development of military personnel. Particular attention is paid to interactive teaching methods, digital learning tools, simulation technologies, and competency-based education approaches. The study highlights how pedagogical technologies contribute to improving military training outcomes, developing critical thinking skills, and preparing military personnel for contemporary security challenges
Keywords: military education; pedagogical technologies; interactive learning